The Development of Alquran and Hadith Integrated Science Module to Improve Student's Religious Character - Prihandoko, Arief; Anggraito, Yustinus Ulung; Alimah, Siti (Universitas Negeri Semarang)
This study aims to test the validity of the integrated science module of the Qur'an and Hadith to improve the religious character of junior high school students, its effectiveness based on cognitive learning outcomes, and the application of religious characters. The research method uses Research and Development, which consists of research, development, validation, and small and large scale trials. The developed module is validated by material experts, media experts, teachers and students. Module testing was carried out using the Times Series Design design on 23 samples of junior high school students. The results of module validation by material experts with fairly valid criteria and media experts with very valid criteria. The teacher response criteria is very valid and the student response is quite valid. Cognitive learning outcomes using modules based on N-gain results have moderate criteria. The applicability of religious characters during learning has moderate criteria.